2005
DOI: 10.1002/pssa.200421177
|View full text |Cite
|
Sign up to set email alerts
|

Study of the products of melamine (C3N6H6) treated at high pressure and high temperature

Abstract: A black‐brown powder was synthesized from melamine (C3N6H6) at 850 °C and 4.5 GPa. There are two possibilities for the sample phase components based on the analyses of C/N/H elements and X‐ray diffraction patterns. One is that the powder is composed of 2H‐type g‐C3N4 and some intermediate phases, while the other is that it consists of some undecomposed raw material, graphite and intermediate phases. The existence of the intermediate phase with long periodicity along one direction is confirmed through transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…According to literature reports on the thermal decomposition of melamine under conventional heating conditions A C H T U N G T R E N N U N G ( 300 8C), melamine would become a linear branching or cyclic condensate with release of ammonia. [31,34,35] This thermal decomposition process is clearly different to that of COA C H T U N G T R E N N U N G (NH 2 ) 2 . Indeed, for the TGA curve of melamine (C 3 H 6 N 6 ), only one decomposition process is observed (see Figure 4 II), suggesting that melamine quickly condenses and sublimates completely under rapid heating.…”
Section: Resultsmentioning
confidence: 89%
“…According to literature reports on the thermal decomposition of melamine under conventional heating conditions A C H T U N G T R E N N U N G ( 300 8C), melamine would become a linear branching or cyclic condensate with release of ammonia. [31,34,35] This thermal decomposition process is clearly different to that of COA C H T U N G T R E N N U N G (NH 2 ) 2 . Indeed, for the TGA curve of melamine (C 3 H 6 N 6 ), only one decomposition process is observed (see Figure 4 II), suggesting that melamine quickly condenses and sublimates completely under rapid heating.…”
Section: Resultsmentioning
confidence: 89%
“…Montigaud et al [9] demonstrated that pyrolysis of melamine at 2.5 GPa and 800 • C in presence of hydrazine leads to formation of a bi-dimensional honeycomb-type structure close to those expected for the theoretical graphitic-like g-C 3 N 4 . Similar syntheses successfully producing g-C 3 N 4 and closely related byproducts utilizing pure melamine have also been achieved [8,10]. Synthesis of C-N nanotubes was also observed in high-pressure catalytic pyrolysis of melamine with NaN 3 -Fe-Ni at 35 MPa and 650 • C [11].…”
mentioning
confidence: 67%
“…46 No g-C 3 N 4 material, which has a relatively strong ~1320 cm -1 band, was formed either. [3][4][5][6] We also investigated thermal decomposition of melamine on TiO 2 in the closed cell with 5 Torr of O 2 initially. The infrared spectral result is shown in Figure S4.…”
Section: Cyanamide Dicyandiamide and Cyanuric Acid On Tiomentioning
confidence: 99%
“…C 3 N 4 . [3][4][5][6][7] As shown in Scheme 1a, melamine can be prepared by mildly heating cyanamide (H 2 N-C≡N) or dicyandiamide ((H 2 N) 2 C=N-C≡N). 8,9 However, upon thermal treatment at a temperature higher than 300 o C, melamine starts to predominantly undergo deamination, instead of ring-breaking process.…”
Section: Introductionmentioning
confidence: 99%